Pemberdayaan Pesantren dalam Optimalisasi Kegiatan Komunikasi melalui Sosialiasi Pencegahan Perilaku Bullying di Kalangan Santri Pondok Pesantren Al-Bunyan - Wina Puspita Sari; Muria Putriana; Asep Soegiarto; Abdul Kholik; Abyan Dwi Martha; Muhammad Reza Firdaus; Nindhiya Salma Haura (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This study discusses the empowerment of Islamic boarding schools in optimizing communication activities through socialization of bullying behavior prevention among students of Al-Bunyan Islamic Boarding School. The focus of research is the role of pesantren as educational institutions that can significantly influence the character and behavior of students. Through the implementation of structured socialization programs, pesantren seeks to raise awareness of the negative impact of bullying and create a supportive and respectful environment. Qualitative methods were used in the study, including interviews, observation, and documentation, to evaluate the effectiveness of the initiative. The research findings show that targeted communication and socialization activities in the context of pesantren can effectively reduce the incidence of bullying, encourage positive interactions between students, and improve the overall welfare of students. This study emphasizes the importance of active involvement and tailored interventions in the educational environment to overcome and reduce bullying behavior as well as the use of digital media as an innovation in curriculum development.